The Views of Primary School Teachers and Parents on Homework at the Primary School Level - Uğraş, Hilal (My University, 2024)
This study aims to determine primary school teachers and parents' views on homework at the primary school level. The research was conducted using a phenomenological design and qualitative research methods. The study group consisted of 27 primary school teachers, who were working in various public schools, and 31 parents of primary school students, all from a province in Türkiye during the 2023–2024 academic year. The research was conducted with the appropriate sampling technique, which is within the scope of purposeful sampling techniques. The researcher created semi-structured interview forms to collect the research data. The researcher used content analysis to describe the research data. The data analysis revealed six main themes that pertain to the opinions of primary school teachers, and five main themes, categories, and codes that reflect the opinions of parents. The study's results revealed that primary school teachers frequently assigned homework to students to reinforce and practice their learning. Parents' support is crucial for the academic, affective, social, and behavioral benefits that homework offers students. The study's results show that parents have positive and negative judgments about homework and assume motivating, guiding, and supervising roles during homework assignments.
Keywords: Primary school; Homework; Primary school teacher; Parents